Introduction to the COVID-19 Special Issue - Bartlett, Maggie; Howden, Stella; Jones, Alison; Martindale, Linda (International Journal of Practice-based Learning in Health and Social Care, 2021)
A special issue exploring innovations and experiences in practice-based learning during the pandemic will be published over the next two editions of the International Journal of Practice-based Learning in Health and Social Care. Focusing on practice-oriented educational activities during the COVID-19 pandemic, the special issue will include research-based, evaluative and reflective articles that capture creativity, development of practice and the experiences of learners and teachers internationally.